Estrategias utilizadas en el entorno de las unidades neonatales para favorecer el mantenimiento de la lactancia materna exclusiva en los primeros 6 meses de edad (2022)
Breast milk is considered the best food that can be offered to the newborn, thanks to the fact that it contains everything necessary for proper growth and development In the processes of childbirth and lactation of natural course where the mother-child bond is established , all these benefits can be taken advantage of, the situation is different for those mothers who present complications and their newborns require hospital care in NICU neonatal units, which makes it impossible to establish breastfeeding, this study aimed to describe what are the strategies used in the environment of neonatal units to favor the maintenance of exclusive breastfeeding in the first 6 months of age through a bibliographic review of the pubmed and scielo databases the results were divided into 5 strategies such as: extraction early breastfeeding, music therapy, professional support group certified and n breastfeeding, kangaroo method for more than 4 hours, non-nutritive suction It was possible to conclude that these strategies significantly improve the production of breast milk and its maintenance during their hospital stay and after discharge. In addition, the importance of training nursing staff is recognized, and the need to create multidisciplinary support groups focused on breastfeeding.